Whole Body Vibration Training Improves Maximal Strength of the Knee Extensors, Time-to-Exhaustion and Attenuates Neuromuscular Fatigue - Serge S. Colson; Jennifer Gioda; Flavio Da Silva (MDPI AG, 2023)
Whole-body vibration (WBV) training programs were reported to improve knee extensor muscle (KE) strength in healthy participants. Unfortunately, the underlying mechanisms of these strength gains remain unresolved. In addition, WBV training was shown to increase the time-to-exhaustion of a static submaximal endurance task. However, the effects of WBV training on neuromuscular fatigue (i.e., a decrease of the maximal voluntary isometric contraction; MVIC) induced by an endurance task is unknown. We, therefore, investigated the influence of WBV training on (i) KE MVIC and neuromuscular function, (ii) the time-to-exhaustion of the KE associated with a submaximal isometric fatiguing exercise, and (iii) KE neuromuscular fatigue and its etiology. Eighteen physically active males were assigned to a WBV group (n = 10) or a sham training group (SHAM; n = 8). The MVIC of the KE, voluntary activation, and electrically evoked responses of the KE were assessed (i) before and after a fatiguing exercise (i.e., submaximal isometric contraction) performed until failure, and (ii) before (PRE) and after a 6-week training (POST) period. At POST, the WBV training increased the KE MVIC (+12%, p = 0.001) and voluntary activation (+6%, p < 0.05) regardless of the fatiguing exercise. The time-to-exhaustion was also lengthened at POST in the WBV group (+34%, p < 0.001). Finally, the relative percentage of MVIC decrease after fatiguing exercises diminished in the WBV group between PRE and POST (−14% vs. −6%, respectively, p < 0.001). Significant neural adaptation enhancements account for the trend in KE strength improvements observed after the WBV training program. In addition, the WBV training was effective at increasing the time-to-exhaustion and attenuating neuromuscular fatigue.